Investigating Anti-diabetic Effects of Autoclaved Curcuma longa Linn (turmeric) Extracts using Mouse Tissues in vitro - Abeer F.R. Alanazi; Esra'a AL-Omari; Abdallah Y. Naser; Norah M. Algahtani; Jim McFarlane (Pharmacology and Clinical Pharmacy Research, 2022)
Curcumin, the active compound found in turmeric, is believed to delay the development of diabetes through several mechanisms. This study aimed to investigate if an aqueous extract of turmeric can improve glucose uptake and uric acid in mouse tissues in vitro, after inclusion of turmeric in the diet for four weeks. Fourteen adult male Swiss mice were divided into three groups. The first group was the control (n=6) that was given clean water, the second group of mice (n=4) was given 5% autoclaved turmeric extract in drinking water, and the third group (n=4) was given 5% non-autoclaved turmeric extract in drinking water. After four weeks, the cardiac muscle, skeletal muscle, pancreas, and liver tissues were dissected and used for analysis.  The results showed that the aqueous 5% turmeric extract reduced glucose in cardiac tissues while the plasma glucose was not changed. Cardiac muscle, liver, pancreas, and skeletal muscle showed glucose absorption after the 5% turmeric treatment. This research shows that turmeric did improve glucose uptake in most tissues, although it was not significant due to the limitations of this study. Tissues may need to be cultured longer and media processed quicker to prevent evaporation. Turmeric continues to show great potential in the treatment of type 2 diabetes and may present an alternative way of treating diabetes.